PEMODELAN TUMPAHAN MINYAK DI TELUK LALONG KABUPATEN BANGGAI - Sabhan, Sabhan; Mudin, Yutdam; Babanggai, Marianus (Univ. Tadulako, 2014)
Oil distribution cause environmental problems that disrupt marine ecosystems and reduce the aesthetic value of coastal waters in Gulf Lalong Banggai. The aims of this study to build a 2D hydrodynamics model to see the patterns of water mass movement and models of oil spill distribution base on the hydrodynamic models in Gulf of Lalong Banggai Regency (0°57'17,3